Evaluasi Kinerja Lembaga Akreditasi Dayah di Aceh: Studi terhadap Efektivitas dan Dampaknya - Mirsal, Ilham; AS, Adnin; Sartina, Karnita; Irwansuri, Zulfan; Rusdi, Muhammad; Noviyani, Rafiqa; Akbar, Muhammad Ali (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2025)
This study aims to evaluate the effectiveness and impact of dayah accreditation bodies in Aceh as instruments for improving the quality of Islamic religious education. The study employs a library research approach with content analysis of scholarly articles, research reports, local regulations such as the Qanun Dayah, and other supporting documents. The findings reveal that the accreditation process has significantly improved dayah management, including the implementation of more systematic documentation, data digitalization, and increased transparency and accountability. Accreditation has also strengthened teachers’ professional competencies through training and fostered a culture of continuous evaluation. However, challenges remain, such as limited human resources, internal resistance to change, administrative burdens, and potential biases that emphasize document completeness over substantive educational quality. Public and stakeholder perceptions of the performance of dayah accreditation bodies are generally positive, as accreditation is viewed as enhancing public trust and the reputation of dayah institutions. Nevertheless, criticisms arise concerning insufficient public dissemination, limited transparency of accreditation results, and concerns that uniform national standards might diminish local cultural identity. The study concludes that dayah accreditation should not be merely an administrative formality but can serve as a transformative strategy for educational quality improvement, if supported by substantive evaluations, harmonization of national standards with local values through the Qanun Dayah, education-based public communication, and active engagement of strategic stakeholders.